'Success in Britain comes with an awful lot of small print': Greg Rusedski and the precarious performance of national identity. Issue 4 (25th April 2020) - Black, Jack; Fletcher, Thomas; Lake, Robert J
Abstract: Sport continues to be one of the primary means through which notions of Englishness and Britishness are constructed, contested, and resisted. The legacy of the role of sport in the colonial project of the British Empire, combined with more recent connections between sport and far right fascist/nationalist politics, has made the association between Britishness, Englishness, and ethnic identity(ies) particularly intriguing. In this paper, these intersections are explored through British media coverage of the Canadian‐born, British tennis player, Greg Rusedski. This coverage is examined through the lens of 'performativity, ' as articulated by Judith Butler. Through a critical application of Butler's ideas, the ways in which the media seek to recognise and normalise certain identities, while problematising and excluding others, can be more fully appreciated. Thus, it was within newspaper framings of Rusedski that hegemonic notions of White Englishness could be performed, maintained, and embedded.